Fundementals of Entrepreneurship (ENT300) Supertive Enterprise / Anis Syazwani Abdul Rahman...[et al.] - Abdul Rahman, Anis Syazwani; Azizan, Ain Nurafaf; Mohd Nazmi, Ayunies Nazzafiqah; Md Zamberi, Anis Aiman; Roslee, Hanan Sofia; Ali Hasmi, Khairuna Qurratu (2019)
Supertive Enterprise is a business that based on sport and recreation. Supertive Enterprise begins it operation on 22 February 2020 which located at Jalan Kledang, 31450 Ipoh, Perak. Next, their target market is teenager and adult. Supertive Enterprise consists of six (6) partners. The price range that Supertive Enterprise offer is only between RM5 – RM20.